Assay methods based on proximity-enhanced reactions for detecting non-nucleic acid molecules - Park, Ye Seop; Choi, Sunjoo; Jang, Hee Ju; Yoo, Tae Hyeon (Frontiers in Bioengineering and Biotechnology, 2023)
Accurate and reliable detection of biological molecules such as nucleic acids, proteins, and small molecules is essential for the diagnosis and treatment of diseases. While simple homogeneous assays have been developed and are widely used for detecting nucleic acids, non-nucleic acid molecules such as proteins and small molecules are usually analyzed using methods that require time-consuming procedures and highly trained personnel. Recently, methods using proximityenhanced reactions (PERs) have been developed for detecting non-nucleic acids. These reactions can be conducted in a homogeneous liquid phase via a single-step procedure. Herein, we review three assays based on PERs for the detection of non-nucleic acid molecules: proximity ligation assay, proximity extension assay, and proximity proteolysis assay. *High robustness, sensitivity, and specificity *Multiple steps for binding with targets and removing non-specific interactions (i.e., heterogeneous) *Trained personnel or automated instruments are needed *Binders may not be available *Sample-to-answer assay time is <4 h *Limit of detection is ~10 −15 M *Can detect the presence of small quantities of a substrate, either antigen or antibody. *Reproducible. LFA (Lateral flow assay) *Simple and fast procedure (i.e., easy to use) * No laboratory equipment and no extensive training required *Lightweight and portable *Long storage stability *Cheapest (e.g., human chorionic gonadotropin (pregnancy) LFAs, are <$1 per test) *Qualitative or semi-quantitative signal with a limited sensitivity *Binders may not be available *False-positive results from prolonged interaction between signaling unit and capture molecules *Sample-to-answer assay time is <15 min *Limit of detection is ~10 −6 M